2017
DOI: 10.3233/jad-161047
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Burden in Obstructive Sleep Apnea

Abstract: Abstract. To test the hypothesis that excessive amyloid deposition is a biological link between obstructive sleep apnea (OSA) and Alzheimer's disease, we determined whether OSA increases cerebral amyloid burden, relative to controls, using Pittsburgh Compound B (PiB) PET imaging. The subjects were adult participants (age 50-65 years) from the Korean Genome and Epidemiology Study. Polysomnography, brain MRI including 3D images, and a detailed neuro-cognitive function test battery were done in 2011-2012. Ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 44 publications
(67 reference statements)
4
61
0
Order By: Relevance
“…Hp may indirectly affect the brain and other target organs, for example, the heart, through the release of numerous cytokines such as TNF‐α acting at a distance. Our own data indicate that Hp‐I increases inflammatory mediators in the blood, including TNF‐α, and contributes to obstructive sleep apnea (OSA) pathophysiology; OSA accelerates amyloid deposition and could contribute to the development or progression of AD . Furthermore, increased TNF‐α secretion and elevated blood TNF‐α levels have been reported by others in patients with CagA‐positive Hp‐I .…”
Section: Helicobacter Pylori and Ad Linkage: Main Hypothesismentioning
confidence: 58%
“…Hp may indirectly affect the brain and other target organs, for example, the heart, through the release of numerous cytokines such as TNF‐α acting at a distance. Our own data indicate that Hp‐I increases inflammatory mediators in the blood, including TNF‐α, and contributes to obstructive sleep apnea (OSA) pathophysiology; OSA accelerates amyloid deposition and could contribute to the development or progression of AD . Furthermore, increased TNF‐α secretion and elevated blood TNF‐α levels have been reported by others in patients with CagA‐positive Hp‐I .…”
Section: Helicobacter Pylori and Ad Linkage: Main Hypothesismentioning
confidence: 58%
“…Historically, there has been an inability to replicate results among the brain imaging studies of SDB in non-demented populations. While several studies have reported gray matter atrophy in the insula, amygdala, middle and lateral temporal regions, and cerebellum in non-demented populations with SDB 1316,4648 , others have either shown no associations 17,49 or paradoxical enhancement in the gray matter volume of regions like the motor cortices, prefrontal cortex, thalamus, putamen, and the hippocampus 2024,47 . In addition, there is a general lack of longitudinal studies, which would enable the study of non-linear associations between SDB and cortical atrophy as suggested by these cross-sectional findings.…”
Section: Discussionmentioning
confidence: 98%
“…Despite numerous studies and meta-analyses focused on the changes in gray matter in middle-aged patients with OSA, there are few studies on gray matter changes in older adults with SDB and neither have found any decreases in thickness or volume in cortical gray matter 5254 . Second, it is possible that SDB-related brain damage impacts more selectively brain function 55 or amyloid burden 17 than gray matter volume alone, or that differential diagnosis between SDB-related and age-related brain atrophy is difficult in single-point observational studies, particulary in those cases in which groups are matched by age and cognitive status. Third, this could also be a sign of: a) survival bias, as most SDB+ may have transitioned to AD and only those with very low cortical atrophy or high in cognitive reserve at disease onset would remain as HC or MCI at cross-section; or, b) selection bias due to matching by the ApoE4 allele, as it has been reported that the ApoE4 allele interacts with brain aging scores measured by the BrainAGE method, revealing potential neuronal compensation in healthy ApoE4+ adults 73 , which could also result in null findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations